Cobalt/zinc dual-sites coordinated with nitrogen in nanofibers enabling efficient and durable oxygen reduction reaction in acidic fuel cells. Issue 7 (29th January 2020) - Zang, Jian; Wang, Feiteng; Cheng, Qingqing; Wang, Guoliang; Ma, Lushan; Chen, Chi; Yang, Lijun; Zou, Zhiqing; Xie, Daiqian; Yang, Hui
Abstract : Co/Zn atomic dual-sites anchored on N doped carbon nanofibers for efficient and durable H2 –O2 fuel cells (∼0.65 V @ 400 mA cm −2, 150 hours). Abstract : The key to reducing the cost of proton-exchange-membrane fuel cells (PEMFCs) is to develop highly efficient non-precious metal catalysts for the oxygen reduction reaction (ORR). Herein, we fabricated Co/Zn atomic dual-sites anchored on N doped carbon nanofibers (Co/Zn–NCNF) via electrospinning, carbonization and post-treatment technologies. Aberration-corrected STEM microscopy verifies the existence of uniformly dispersed Co/Zn atomic pairs within the NCNF. X-ray adsorption fine structure spectroscopy combined with the fitting and calculated results further ascertain the coordination structure of Co/Zn dual-sites with a configuration of N2 CoN2 ZnN2 . Such a Co/Zn–NCNF catalyst exhibits greatly enhanced ORR activity with onset and half-wave potentials of 0.997 V and 0.797 V/RHE in an acidic electrolyte, compared to the Co or Zn mono-doped sample. Density functional theory calculations reveal that the novel N2 CoN2 ZnN2 structure, different from the traditional Co–N4 or Zn–N4, could largely lower the dissociative barrier of the *OOH intermediate during the ORR, thereby boosting the electrocatalytic activity. Finally, the H2 –O2 PEMFC assembled using Co/Zn–NCNF as a cathodic catalyst displays a maximum power density of 0.603 W cm −2 together with a remarkable stability of ca. 0.65 V after 150 h discharging at a current density of 400 mA cm −2, paving the way for the future development of non-precious metal PEMFCs.